2017
DOI: 10.1080/15622975.2017.1369566
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipids metabolism in mild cognitive impairment and Alzheimer’s disease

Abstract: Lipids metabolites in plasma might indirectly indicate changes in neuronal membrane and this deregulation can outline the transition between healthy and diseased brains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Nevertheless, this was not especially surprising, as many authors have repeatedly reported inconsistent results and unsatisfactory validation of metabolomicsbased biomarkers. [40][41][42][43] Growing evidence points that one of the most important challenges for biomarker validation studies in the metabolomics field could be the high intra-and interindividual variability of the human metabolome, which can arise from genetic (e.g., gender), temporal (e.g., circadian rhythm), environmental (e.g., dietary habits) or microbial (e.g., eubiosis/dysbiosis) factors. [44] This variability may result in different, but analogous, metabolic responses (e.g., different metabolites from the same metabolic pathway) to a given physiological or pathological stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this was not especially surprising, as many authors have repeatedly reported inconsistent results and unsatisfactory validation of metabolomicsbased biomarkers. [40][41][42][43] Growing evidence points that one of the most important challenges for biomarker validation studies in the metabolomics field could be the high intra-and interindividual variability of the human metabolome, which can arise from genetic (e.g., gender), temporal (e.g., circadian rhythm), environmental (e.g., dietary habits) or microbial (e.g., eubiosis/dysbiosis) factors. [44] This variability may result in different, but analogous, metabolic responses (e.g., different metabolites from the same metabolic pathway) to a given physiological or pathological stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…With links between cardiovascular disease and AD being drawn, as well as some promising results from lifestyle intervention on cognitive performance [67], lipid evaluation has become another area of interest in the search for blood-based biomarkers of AD. Two recent pilot studies have shown levels of lipids to differ significantly between mutation carriers and non-carriers in a study on familial AD [68], as well as AD and controls in a sporadic AD study [69]. However, neither study was able to use these profiles to accurately discriminate between the respective classes.…”
Section: Metabolomicsmentioning
confidence: 93%
“…A new technique, which uses brain-focused ultrasound (FUS) ( Costa, Joaquim, Forlenza, Talib, & Gattaz, 2019 ) to sonicate systematically administered microbubbles, can reversibly and locally disrupt tight junctions ( Shang, Wang, Liu, Zhang, & Xue, 2011 ; Sheikov, McDannold, Sharma, & Hynynen, 2008 ) and increase active transcytosis in the BBB ( Sheikov et al, 2006 ), allowing antibody transport from the blood to specific brain regions. This method was found to be safe in non-human primates ( McDannold, Arvanitis, Vykhodtseva, & Livingstone, 2012 ; Nwagwu et al, 2020 ), and recently in humans ( Abrahao et al, 2019 ; Carpentier et al, 2016 ).…”
Section: Fcrn and Cellular Barriersmentioning
confidence: 99%